Effect of Chilling Duration on Post‐Thaw Characteristics of Sperm from the North American bison (Bison bison). Issue 4 (2nd January 2013) - Krishnakumar, S; Whiteside, D; Dance, A; Elkin, B; Thundathil, J
Contents: The objective of this study was to determine the duration for which sperm from the North American bison ( Bison bison ) could be chilled prior to being cryopreserved, without compromising post‐ thaw sperm quality. This would permit transport of samples collected remotely, to the laboratory (at 4°C) for cryopreservation. Epididymal sperm from plains bison (n = 11) and ejaculated sperm from wood bison (n = 3) were collected, extended and held at 4°C for extended periods of time. At intervals, an aliquot was cryopreserved. Post‐thaw sperm motion characteristics were evaluated by computer assisted sperm analysis. Representative plains bison sperm samples (n = 3) were evaluated for their in vitro fertilizing ability in a heterologous system using bovine oocytes. There was no statistical difference in total and progressive motility of plains bison epididymal sperm when cryopreserved after chilling for 24, 48 or 72 h. For wood bison ejaculated sperm, there was no difference in total and progressive motility for sperm cryopreserved following 24 or 48 h of chilling. However, one of the three bulls showed significantly poorer fertilization (based on cleavage rate) with sperm chilled for 72 compared to 24 and 48 h prior to freezing. In conclusion, plains bison epididymal sperm can be chilled for 72 h and wood bison ejaculated sperm can be chilled for at least 48 h prior to cryopreservation without compromising post‐thaw sperm motility, while heterologous in vitro fertilization (IVF) assay indicated a between‐bull variation in the in vitro fertilizing ability of sperm chilled for an extended duration before cryopreservation.